Chronic mitral regurgitation detected on cardiac MDCT: differentiation between functional and valvular aetiologies. - Killeen RP; Arnous S; Martos R; Abbara S; Quinn M; Dodd JD; Killeen, Ronan P; Arnous, Samer; Martos, Ramon; Abbara, Suhny; Quinn, Martin; Dodd, Jonathan D (European Radiology, 2010)
Objective: To determine whether cardiac computed tomography (MDCT) can differentiate between functional and valvular aetiologies of chronic mitral regurgitation (MR) compared with echocardiography (TTE).Methods: Twenty-seven patients with functional or valvular MR diagnosed by TTE and 19 controls prospectively underwent cardiac MDCT. The morphological appearance of the mitral valve (MV) leaflets, MV geometry, MV leaflet angle, left ventricular (LV) sphericity and global/regional wall motion were analysed. The coronary arteries were evaluated for obstructive atherosclerosis.Results: All control and MR cases were correctly identified by MDCT. Significant differences were detected between valvular and control groups for anterior leaflet length (30 +/- 7 mm vs. 22 +/- 4 mm, P < 0.02) and thickness (3.0 +/- 1 mm vs. 2.2 +/- 1 mm, P < 0.01). High-grade coronary stenosis was detected in all patients with functional MR compared with no controls (P < 0.001). Significant differences in those with/without MV prolapse were detected in MV tent area (-1.0 +/- 0.6 mm vs. 1.3 +/- 0.9 mm, P < 0.0001) and MV tent height (-0.7 +/- 0.3 mm vs. 0.8 +/- 0.8 mm, P < 0.0001). Posterior leaflet angle was significantly greater for functional MR (37.9 +/- 19.1 degrees vs. 22.9 +/- 14 degrees , P < 0.018) and less for valvular MR (0.6 +/- 35.5 degrees vs. 22.9 +/- 14 degrees, P < 0.017). Sensitivity, specificity, and positive and negative predictive values of MDCT were 100%, 95%, 96% and 100%.Conclusion: Cardiac MDCT allows the differentiation between functional and valvular causes of MR.